PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN HPP UNTUK UMKM ABON IKAN DI DESA SEBONG PEREH - Alamsyahbana, M. Isa; Sulastri, Dini; Jacky, Jacky; Pramita, Maharani Eka; Audina, Yulia Putri; Nurmalasari, Nurmalasari; Wulandari, Wina; Fajriyani, Suzan; Gunawan, Syahrul; Nursyalim, Alwi Dwi; Mareta, Karina Vivinanda (P3M STIE Pembangunan Tanjungpinang, 2025)
Micro, Small and Medium Enterprises located in the Bintan Island area mostly do not have or are unable to prepare simple financial reports, even though the role of simple financial records is very important in an MSME business unit, because having financial records certainly makes it easier for businesses to monitor income and expenses in the business and what kind of selling price must be set so that the business makes a profit.The factor that causes difficulty in preparing simple financial reports for Micro, Small and Medium Enterprises is the absence of a clear economic entity. This happens because most MSMEs are unable to differentiate between business activities and personal activities, so company assets are recognized as personal property and vice versa. From this statement, it is difficult to clearly identify the economic entity.This research was conducted at the UMKM